Building drainage in dense urban areas - Dmitirev, Dmitro; Perlova , Olena (Academic journal Industrial Machine Building Civil Engineering, 2024)
This article analyzes the specific challenges of constructing underground structures under complex hydrogeological conditions in densely built-up urban environments. The construction of pile foundations, tunnels, utility networks, and underground parking areas often obstructs natural groundwater flow, leading to localized flooding. The underground space of a modern city is saturated with water-bearing utility lines prone to unpredictable leaks. In such cases, it is essential to preserve the existing hydrogeological regime and prevent additional structural deformations of adjacent buildings. Therefore, the regulatory framework for the protection of underground structures must be improved in accordance with contemporary engineering standards.
Keywords: hydrogeological conditions; groundwater level; construction dewatering; filtration coefficient; needle filters